Methanol Effect on color stability and shelf life of phenolic Resin compound under acidic conditions - Waadallah Ahmed, Ammar (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
The object of this work is to investigate the effect of the addition of methanol on the shelf life and color characteristics of novolak resin. Different percentages were added and two mechanisms were suggested for the addition. High ortho structure (1, 2-3) novolak resin was prepared and used in the above investigation. Experimental determination using FT-IR and UV-spectroscopy showed that on the addition of 30% of methanol and according to the second mechanism of addition novolak shelf life increased to 12 months without obvious decomposition and color change. It is suggested that methanol plays an important role in the inhabitation of the reactive sites on the resin that are responsible for the oxidation of the polymer when exposed to atmospheric or storage conditions.